Influence of various factors on individual radiation exposure from the chernobyl disaster - Bondar Alexandra; McCarthy Philip; Mahoney Martin C; Moysich Kirsten B; Zamostian Pavlo; Noschenko Andrey G; Michalek Arthur M (BMC, 2002)
Abstract Background The explosion at the Chernobyl Nuclear Power Plant was one of the greatest known nuclear disasters of the 20th century. To reduce individual exposure to ionizing radiation the Soviet Union government introduced a number of counter-measures. This article presents a description of how historical events conspired to disrupt these efforts and affect residents in exposed areas. Methods This study employed an extensive review of data on radionuclide deposition, contamination patterns and lifestyle characteristics. Data were obtained from the Ukraine Ministry of Health and the Ukraine Research Center for Radiation Medicine. Results Data are presented on annual contamination rates in selected locales as well as data on local food consumption patterns. Historical factors including economic and political circumstances are also highlighted. Results show the diminution of individual doses between 1987 and 1991 and then an increase between 1991 and 1994 and the relationship between this increase and changes in the lifestyle of the local population. Conclusion A number of factors played direct and indirect roles in contributing to the populace's cumulative radiation exposure. Future post-contamination studies need to consider these factors when estimating individual exposures.